A cross‐sector systematic review and synthesis of knowledge on telemedicine interventions in chronic wound management—Implications from a system perspective. Issue 5 (19th October 2022) - Høyland, Sindre Aske; Holte, Kari Anne; Islam, Kamrul; Øygaarden, Olaug; Kjerstad, Egil; Høyland, Synnøve Aske; Wærnes, Hanne Rusten; Gürgen, Marcus; Conde, Katharina Brekke; Hovland, Kristin Søisdal; Rødseth, Eirin; Carayon, Pascale; et al.
Abstract: Based on initially identified needs for further telemedicine (TM) and chronic wound management research, the objective of this article is twofold: to conduct a systematic review of existing knowledge on TM interventions in chronic wound management—including barriers and opportunities—across the specialist and primary care sectors, and to incorporate the review findings into a system framework that can be further developed and validated through empirical data. We conclude that there is a pressing need for broader and more comprehensive empirical explorations into quality improvement and integration of TM in chronic wound management, including using system frameworks that can capture cross‐sector system perspectives and associated implications. Of practical consideration, we suggest that the design and execution of TM improvement interventions and associated research projects should be conducted in close cooperation with managers and practitioners knowledgeable about barriers and opportunities that can influence the implementation of important interventions within chronic wound management.